Microstrip side-couple ring filter at 1.8GHz with 10% bandwidth / Abdul Rahman Ab Razak - Ab Razak, Abdul Rahman (2010)
This thesis is presents the study of microstrip side-couple ring filter using the same concept as dual-band ring resonator. The basic structure of the filter designed is the dual mode ring resonator cascaded with quarter-wavelength side-coupled lines. The filter is designed at 1.8 GHz as central frequency with 10% bandwidth. The microstrip filter is implemented with £r=5.4 and 1.6mm thickness. The main component such circuit layout, simulation and measurement are presented in this paper.